UPAYA PENINGKATAN KINERJA PELAYANAN SURAT KETERANGAN CATATAN KEPOLISISAN (SKCK) DI POLRES SLEMAN (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
This study aims to improve the service of SKCK (Police Records Certificate) at the Sleman Police. Data collection techniques by interview, observation and literature study. The problem discussed is the performance of the Sleman Police in the service of the Police Record Certificate (SKCK) which is not yet optimal. The purpose of this study was to find out the obstacles that resulted in the SKCK service not being optimal at the Sleman Police, to find out the efforts made to overcome the problem of the non-optimal SKCK service at the Sleman Police. This research is oriented to qualitative descriptive, namely research that describes or describes the results of data collection and processing along with information from sources. The results showed that: 1) Obstacles in SKCK services at Polres Sleman were: a) Lack of technology updates and their mastery by officers. b) Insufficient number of officers. c) Facilities and infrastructure are limited in number. d) The service area is less spacious. 2) Efforts made so that SKCK services can be optimal are: a) Creating an online application for online SKCK applications. b) The need for additional service personnel. c) Training or capacity building for officers. d) Addition of facilities and infrastructure to support services such as generators, computers and laptops. e) Expansion of SKCK service places and facilities for persons with disabilities.
Keywords: Performance; Service.